2007
DOI: 10.1159/000098253
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Classification of Proliferative Diabetic Vitreoretinopathy

Abstract: Purpose: To review the current knowledge regarding the pathogenesis of proliferative diabetic vitreoretinopathy (PDVR) and to present recommendations for its clinical staging. Design: Focused literature review and authors’ clinical experience. Results: Although several biochemical mediators may be responsible for the pathogenesis of PDVR, no common biochemical pathway exists. Of those mediators, vascular endothelial growth factor is the one most studied so far. However, since in proliferative diabetic retinopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 195 publications
5
69
1
6
Order By: Relevance
“…The most important determinants for the beginning and progression of DR and diabetic macular oedema are disease duration and the level of metabolic control (glycosylated haemoglobin, HbA 1c , level) [4][5][6][7][8][9] . The manifestation and the progression of DR are modified by multiple systemic factors such as arterial hypertension [1,6,8,10,11] , dyslipidaemia [4,6,8,12] , microalbuminuria [13] , insulin treatment [11] and ocular perfusion pressure [5] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important determinants for the beginning and progression of DR and diabetic macular oedema are disease duration and the level of metabolic control (glycosylated haemoglobin, HbA 1c , level) [4][5][6][7][8][9] . The manifestation and the progression of DR are modified by multiple systemic factors such as arterial hypertension [1,6,8,10,11] , dyslipidaemia [4,6,8,12] , microalbuminuria [13] , insulin treatment [11] and ocular perfusion pressure [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The manifestation and the progression of DR are modified by multiple systemic factors such as arterial hypertension [1,6,8,10,11] , dyslipidaemia [4,6,8,12] , microalbuminuria [13] , insulin treatment [11] and ocular perfusion pressure [5] . However, their exact contribution to DR pathogenesis is in most cases unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para classificar a retinopatia diabética proliferativa (RDP) foi usada a classificação descrita por Kroll et al, que diferencia os estágios da doença baseados em alterações morfológi-cas como segue: Estágio A, Estágio B fase Bn e Bt, Estágio C1-C4 (10)(11) . Foi avaliada a relação da retinopatia diabética com sexo, idade, tempo estimado de diagnóstico, nível de glicemia, nefropatia, hipercolesterolemia, acuidade visual, ní-vel de hemoglobina glicosilada e quanto à presença sistêmica de hipertensão arterial.…”
Section: Resumo Introduçãounclassified
“…5 Studies have found that VEGF is involved in the pathogenesis of diabetic complications. [6][7][8] Hyperglycemia-induced diacylglycerol, a lipid molecule, activates protein kinase C in the vascular tissues, and the latter in turn promotes VEGF signaling, resulting in diabetic microvascular complications. 9 Other factors, including hypoxia, gender, smoking, elevated levels of blood lipids, inflammatory status, and activated stress axes, may affect the synthesis and secretion of VEGF; among them, the major physiological stimulus for VEGF expression is the cellular hypoxia.…”
Section: Introductionmentioning
confidence: 99%